CP-673451, a Selective Platelet-Derived Growth Factor Receptor Tyrosine Kinase Inhibitor, Induces Apoptosis in Opisthorchis viverrini-Associated Cholangiocarcinoma via Nrf2 Suppression and Enhanced ROS - Jinchutha Duangdara; Boonyakorn Boonsri; Apinya Sayinta; Kittiya Supradit; Pakpoom Thintharua; Supeecha Kumkate; Chinnawut Suriyonplengsaeng; Noppadol Larbcharoensub; Somkit Mingphruedhi; Narongsak Rungsakulkij; Paramin Muangkaew; Pongsatorn Tangtawee; et al. (Pharmaceuticals, 2023)
Platelet-derived growth factors (PDGFs) and PDGF receptors (PDGFRs) play essential roles in promoting cholangiocarcinoma (CCA) cell survival by mediating paracrine crosstalk between tumor and cancer-associated fibroblasts (CAFs), indicating the potential of PDGFR as a target for CCA treatment. Clinical trials evaluating PDGFR inhibitors for CCA treatment have shown limited efficacy. Furthermore, little is known about the role of PDGF/PDGFR expression and the mechanism underlying PDGFR inhibitors in CCA related to Opisthorchis viverrini (OV). Therefore, we examined the effect of PDGFR inhibitors in OV-related CCA cells and investigated the molecular mechanism involved. We found that the PDGF and PDGFR mRNAs were overexpressed in CCA tissues compared to resection margins. Notably, PDGFR-α showed high expression in CCA cells, while PDGFR-β was predominantly expressed in CAFs. The selective inhibitor CP-673451 induced CCA cell death by suppressing the PI3K/Akt/Nrf2 pathway, leading to a decreased expression of Nrf2-targeted antioxidant genes. Consequently, this led to an increase in ROS levels and the promotion of CCA apoptosis. CP-673451 is a promising PDGFR-targeted drug for CCA and supports the further clinical investigation of CP-673451 for CCA treatment, particularly in the context of OV-related cases.